Heinz Hartmann and Dora Hartmann papers - Hartmann, Heinz, 1894-1970.; Hartmann, Dora, 1902-1974.; Hartmann, Heinz, 1894-1970
Correspondence, memoranda, writings, minutes, reports, patient files, bylaws, brochures, lists, printed material, and other papers relating primarily to the Hartmanns's work in the field of psychoanalysis chiefly with the New York Psychoanalytic Institute and other psychoanalytical organizations and in his writing and editorial projects, especially The Psychoanalytic Study of the Child of which he was cofounder and editor, 1945-1970. Dora Hartmann's papers pertain to her work with the New York Psychoanalytic Institute. Correspondents include Princess Marie Bonaparte, Otto Fenichel, Anna Freud, Ernst Kris, Lawrence S. Kubie, Sacha Nacht, Max Schur, and Martin H. Stein.
Heinz Hartmann, psychoanalyst and author, and Dora Karplus Hartmann, psychoanalyst and educator.
Collection material in English, German, French, and shorthand.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Bonaparte, Marie, -- Princess, -- 1882-1962 -- Correspondence; Fenichel, Otto -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Kris, Ernst, -- 1900-1957 -- Correspondence; Kubie, Lawrence S. -- 1896-1973 -- Correspondence; Nacht, Sacha, -- 1901-1977 -- Correspondence; Schur, Max -- Correspondence; Stein, Martin H. -- Correspondence; New York Psychoanalytic Institute; Child analysis -- Periodicals; Psychoanalysis; Psychoanalysis -- Societies, etc; Authors; Psychoanalysts